Biculturalism and Spanish in contact sociolinguistic case studies - Núñez Méndez, Eva 1970- (Routledge studies in Hispanic and Lusophone linguistics, 2019)
"Biculturalism and Spanish in Contact: Sociolinguistic Case Studies provides an original and modern analysis of the development of Spanish and its contact with other languages using a sociolinguistic framework from both synchronic and diachronic angles. Split into three sections, (i) Border speech communities, (ii) Outcomes and perceptions in situations of language and dialect contact and (iii) Contact and alternation: social boundaries of language switching, this collection offers new perspectives in the field of language contact and change. Each chapter presents an original study detailing the social factors that have shaped contact varieties of Spanish, providing principal arguments and theories about language use, contact, and change, as well as guided topics for discussion. With its wide scope, this book is a landmark in language interaction processes and studies, and will be a valuable reference for educators, scholars, language professionals and students with an interest in the vitality of the Spanish language in contact with other languages"--